2018
DOI: 10.2903/j.efsa.2018.5460
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of Monteban® G100 (narasin) for chickens for fattening

Abstract: The feed additive Monteban® G100, containing the active substance narasin, an ionophore anticoccidial, is intended to control coccidiosis in chickens for fattening at a dose of 60–70 mg/kg complete feed. Narasin is produced by fermentation. Limited data on the taxonomic identification of the production strain did not allow the proper identification of strain NRRL 8092 as Streptomyces aureofaciens. The FEEDAP Panel cannot conclude on the absence of genetic determinants for antimicrobial resistance in Streptomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…In its opinion on the safety and efficacy of Monteban ® G100 containing narasin produced by the same microorganism (EFSA FEEDAP Panel, ), the FEEDAP Panel concluded that: ‘Limited data on the taxonomic identification of the production strain did not allow the proper identification of strain NRRL 8092 as Streptomyces aureofaciens . The FEEDAP Panel cannot conclude on the absence of genetic determinants for antimicrobial resistance in Streptomyces spp.…”
Section: Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In its opinion on the safety and efficacy of Monteban ® G100 containing narasin produced by the same microorganism (EFSA FEEDAP Panel, ), the FEEDAP Panel concluded that: ‘Limited data on the taxonomic identification of the production strain did not allow the proper identification of strain NRRL 8092 as Streptomyces aureofaciens . The FEEDAP Panel cannot conclude on the absence of genetic determinants for antimicrobial resistance in Streptomyces spp.…”
Section: Assessmentmentioning
confidence: 99%
“…The holder of the authorisation of Maxiban ® G160 and Monteban ® G100 is the same and narasin from Maxiban ® G160 is applied at the same maximum concentration as narasin from Monteban ® G100. The applicant submitted the same literature search on the tolerance of narasin in poultry covering the period 2000–2014 using several databases that has been assessed by the FEEDAP Panel in 2018 in its opinion on the safety and efficacy of Monteban ® G100 for chickens for fattening (EFSA FEEDAP Panel, ) . The applicant claimed that no papers relevant to the safety of the target species were identified…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations